2020
DOI: 10.1049/iet-pel.2019.0831
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparisons between frequency‐domain analysis and time‐domain analysis for LLC resonant converter

Abstract: LLC resonant converter has been widely used in many applications due to its characteristics of high efficiency and high frequency characteristics. Analysis method plays great role in converter design and operation performance. For LLC resonant converter, the most frequently used analysis methods are frequency-domain analysis (FDA) and time-domain analysis (TDA). FDA assumes that only fundamental harmonics can deliver energy in the system, while TDA is obtained by solving circuit state equations. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Based on the Euler-Bernoulli beam theory, the governing equations of the system are derived [10]. Wei et al concluded that based on the robust control method, the vibration control problem of a piezoelectric smart beam structure was analyzed [11]. erefore, the author proposes to use the TMDI system to control the vibration electricity of the beam structure under the action of seismic acceleration and moving force, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the Euler-Bernoulli beam theory, the governing equations of the system are derived [10]. Wei et al concluded that based on the robust control method, the vibration control problem of a piezoelectric smart beam structure was analyzed [11]. erefore, the author proposes to use the TMDI system to control the vibration electricity of the beam structure under the action of seismic acceleration and moving force, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The spatial-timedomain period analysis of audio coded signals is mainly considered to have two important research aspects: one part is the spatial-time-domain period analysis, that is, the various time-domain period waveforms of different audio coded signals are used as custom variables to study various differences [8]. Comprehensive analysis, the basic principle of which is to use Fourier transform through frequency modulation to decompose all audio signals that need to be collected at the same time to form a series of orthogonal cosine spectrum components of different signal frequencies for superimposition [9]. The literature analyzes the characteristics of wireless sensor networks and their application elds and wide range of applications through research and analysis, discusses the deployment and coverage of wireless sensor networks, as well as the problems in the construction of sensor networks, and the deployment and coverage of sensor networks [10].…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, the effect of resonant current on ZVS is ignored. In [19], frequency domain analysis and time domain analysis are used as a comparison to design LLC. The realization of ZVS is based on the fact that the resonant current lags behind the resonant network input voltage.…”
Section: Ac/dc (Pfc)mentioning
confidence: 99%
“…But in boost region, the magnetizing inductor current no longer changes linearly. Thus, the calculation of the critical current in [18,19], [21] and [23] can not be used to judge the soft switching situation.…”
Section: Ac/dc (Pfc)mentioning
confidence: 99%